Trend of malaria incidences and its association with rainfall in Kalahandi District of Odisha, India - Martand Mani Mishra; Netrananda Sahu; Gayatri Mallick; Balaram Pani (Wolters Kluwer Medknow Publications, 2023)
In Odisha, Kalahandi is one of the most exposed and vulnerable districts to malaria incidences due to its poor socioeconomic condition and extreme climate. The study aimed to explore the temporal characteristics of malaria incidences in Kalahandi and to identify its relationship with rainfall for the period from 2011 to 2018. Out of the total blood films examined, 8.84% were found positive in Kalahandi between 2011 and 2018. Plasmodium falciparum is the most dominant species accounted 88.3% of the total cases. Very high mean annual parasitic index (API) >15 is recorded throughout the study years. The highest incidences are recorded in the monsoon season followed by postmonsoon. The correlation value of the annual blood examination rate with P. falciparum, Plasmodium vivax, and API has shown a very high positive correlation. Rainfall shows a (+) correlation with malaria incidences in the cold (0.47) and hot seasons (0.01) and (−) correlation in the monsoon (−0.54) and postmonsoon season (−0.54).